Ethical Perceptions Of Accounting Students: The Role Of The God Locus Of Control, Moral Disengagement, And Love Of Money - Amelia Oktrivina; Achmadi Achmadi; Hendryadi Hendryadi (Universitas Muhammadiyah Malang, 2022)
The present study attempts to examine the effect of the God locus of control on ethical perceptions of accounting students and then further explore the psychological mechanism underlying this effect. We established a mediation and moderation model based on social cognitive theory and locus of control theory in which moral disengagement as mediator and love of money as moderator on the God locus of control and ethical perceptions. This study involved 324 participants through a series of online questionnaires. The moderated mediation analysis using Hayes's Macro Process demonstrated that the God locus control was negatively associated with moral disengagement and positively related to ethical perception. Moral disengagement is negatively associated with ethical perception and partially mediates the relationship between the God locus of control and ethical perception. As expected, the love of money plays an essential role as a boundary condition in the relationship between the God locus of control and ethical perceptions, but not for moral disengagement and ethical perceptions relationship. This study is the first empirical evidence to explore the role of the God locus of control on moral disengagement and ethical perceptions.